PERANCANGAN SISTEM INFORMASI PENGELOLAAN ASRAMA DI LEMBAGA PENJAMINAN MUTU PENDIDIKAN (LPMP) BANTEN MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT (RAD) - Sutanto Sutanto; Widyawati Widyawati; Ari Anjayatno (Jurnal Ilmiah Sains dan Teknologi, 2020)
Education Quality Assurance Institution of Banten (LPMP) is one of the Technical Subsudiary Units (UPT) of the Ministry of Education and Culture in Banten Province which has facilities and infrastructure in the form of dormitories, guesthouses, halls, auditoriums and classes that are used as lodging facilities in activities education and training or technical guidance activities for teachers in the Banten Province. The Dormitory Management System at the Banten Education Quality Assurance Institute (LPMP) since its establishment in 2003 until now still uses conventional methods, that is, all transactions starting from ordering to using dormitory / building facilities by recording all data in books and whiteboards. The Research Method used in this Thesis uses the Rapid Aplication Development (RAD). Optimal application of the Dormitory Management Information System at the web-based Banten Quality Assurance Institute (LPMP) from scheduling activies to plotting rooms for guests can help synchronize between BMN managers, activity coordinators and dormitory staff in use of dormitories/buildings in Banten Education Quality Assurance Institute (LPMP).